THE EFFECT OF SERVICE QUALITY, HOSPITAL FACILITIES, AND PATIENT SATISFACTION ON PATIENT LOYALTY - Leony Martila; Kosasih (RADJA PUBLIKA, 2026)
This study examines the influence of service quality, hospital facilities, and patient satisfaction on patient loyalty in healthcare institutions. Patient loyalty represents a strategic goal for hospitals, as it ensures sustainable retention, enhances reputation, and reduces marketing costs associated with acquiring new patients. The research employs a literature review method, analyzing previous empirical studies and theoretical frameworks related to healthcare service quality, facilities, patient satisfaction, and loyalty. Service quality is conceptualized through both technical and functional dimensions, encompassing accurate diagnosis, effective treatment, empathetic staff interactions, and responsiveness. Hospital facilities include physical infrastructure, medical equipment, room comfort, cleanliness, accessibility, and environmental factors that contribute to patients’ overall experience. Patient satisfaction serves as both an outcome of service quality and facilities and a mediating factor that translates positive perceptions into loyal behaviors. The results indicate that service quality and hospital facilities individually and jointly have a significant effect on patient satisfaction, which in turn strongly influences patient loyalty. High service quality enhances trust, confidence, and emotional attachment, while superior facilities provide tangible evidence of professionalism and care.